Implications of EMU for Exchange Rate Policy in Central and Eastern Europe - Kopits, George (IMF Working Papers; Working Paper, 1999)
In view of the requirements of Stage 2 of European Monetary Union (EMU) for accession to the European Union, this paper examines the desirability for, and the ability of, the lead candidates in Central and Eastern Europe to participate in the new exchange rate mechanism (ERM2) and eventually in EMU. For most of these countries the benefits are likely to outweigh the cost of participation. After successfully meeting the basic conditions (wage flexibility, prudent fiscal and monetary stance, financial system soundness) for ERM2, each candidate should be able to shadow the euro, with sufficient flexibility around the central rate, prior to formal participation. The paper concludes with a discussion of two policy dilemmas.